Hemodynamic Effects of Stent-Induced Straightening of Parent Artery vs. Stent Struts for Intracranial Bifurcation Aneurysms - Wan, Hailin; Lu, Gang; Ge, Liang; Huang, Lei; Jiang, Yeqing; Leng, Xiaochang; Xiang, Jianping; Zhang, Xiaolong (Frontiers in Neurology, 2022)
Objective This study aims to compare the hemodynamic impact of stent-mesh and stent-induced straightening of the parent artery in intracranial bifurcation aneurysms using finite element method simulation. Material and Methods Three intracranial bifurcation aneurysms treated with different stent-assisted coil embolization were evaluated. Simulation using the finite element method was conducted for Solitaire, LVIS and Neuroform stents. Four models of each stent were established, including a pre-treatment baseline, stenting without parent artery straightening (presented as stent-mesh effect), no-stent with parent artery reconstruction (to reveal the straightening impact), and stenting with straightening (categorized as Models I–IV respectively). Hemodynamic characteristics of the four models for each stent were compared. Results In the Neuroform stent, compared with the pre-treatment model (100%), the mean WSS decreased to 82.3, 71.4, and 57.0% in Models II-IV, velocity to 88.3, 74.4, and 62.8%, and high flow volume (HFV, >0.3 m/s) to 77.7, 44.0, and 19.1%. For the LVIS stent, the mean WSS changed to 105.0, 40.2, and 39.8% in Models II to IV; velocity to 91.2, 58.1, and 52.5%, and HFV to 92.0, 56.1, and 43.9%. For the Solitaire stent, compared with the pre-treatment model (100%), the mean WSS of Models II-IV changed altered by 105.7, 42.6, and 39.4%, sac-averaged velocity changed to 111.3, 46.6, and 42.8%, and HFV 115.6, 15.1, and 13.6%. Conclusion The hemodynamic effect of straightening the parent artery of intracranial bifurcation aneurysms by stenting was noticeably improved over stent mesh diversion in all three stents tested. Therefore stent-induced remodeling of the parent artery appears to be the best method of decreasing recurrence in intracranial bifurcation aneurysms.